Predicting factors of intimidation among coetaneans from the perception of teachers and high school students - García Ampudia, Lupe (2013)
Intimidation among coetaneans is a complex problem which is made up of not only the direct protagonists who are the students but also the teachers who interact permanently in the classroom and the educational centre. The goals are oriented to identify the predicting factors of the intimidation among coetaneans, perceived from the different roles (teacher, student), compare the perception of personal, family and socio-educative factors of the intimidation in students and teachers of different genre. The design of the research project is descriptive-comparative, the sample is 606 students and 70 teachers, all of them come from public high schools. The results establish meaningful differences in the perception of predicting factors of intimidation among coetaneans according to the role: teachers and students, from the perspective of genre, meaningful differences in the personal and family factor were found and no differences were found in the socio-educative factor.